Two dimensional layered electron transport bridges in mesoscopic TiO2 for dye sensitized solar cell applications. (20th March 2018) - Gopakumar, Gopika; Menon, Harigovind; Ashok, Aditya; Nair, Shantikumar V.; Shanmugam, Mariyappan
Abstract: The present work demonstrates the possibility of facilitating electron transport in mesoscopic titanium dioxide (TiO2 ) by incorporating nanoflakes of layered molybdenum disulfide (MoS2 ) as an alternate electron transport bridge. Results suggest that performance of dye sensitized solar cells (DSSCs) can be increased up to ∼16% (from 7.39% to 8.55%) by incorporating 0.2 wt % of MoS2 into the bulk of TiO2, due to the significant improvement in electron lifetime from 8 ms to 23 ms. The nanoflakes of MoS2 form alternate electron transport bridges in the bulk TiO2 nanoparticle film through which photo-injected electrons travel more efficiently to reach transparent electrode compared to DSSCs utilize only TiO2 without MoS2 . Presence of atomically thin layered MoS2 nanoflakes in the bulk of TiO2 assist the photo-electrons to skip electron-hole capture processes occur through TiO2 surface states to avoid the interfacial recombination. Further increment in the concentration of MoS2 suppresses the resulting DSSC performance by blocking the porosity which results in less dye adsorption and hence lower photocurrent values. Graphical abstract: 2D Layered MoS2 in TiO2 facilitates charge transport and improves DSSC performance. Image 1